Latest performance results from the font5 intra-train beam position and angle feedbacksystem at ATF2 - Bett, DR; Blaskovic Kraljevic, N; Burrows, P; Christian, G; Davis, MR; Perry, C; Apsimon, R; Constance, B; Gerbershagen, A; Resta Lopez, J (2012)
A prototype Interaction Point beam-based feedback system for future electron-positroncolliders, such as the International Linear Collider, has been designed and tested on theextraction line of the KEK Accelerator Test Facility (ATF). The FONT5 intra-train feedbacksystem aims to stabilize the beam orbit by correcting both the position and angle jitter inthe vertical plane on bunch-tobunch time scales, providing micron-level stability at theentrance to the ATF2 final-focus system. The system comprises three stripline beam positionmonitors (BPMs) and two stripline kickers, custom low-latency analogue front-end BPMprocessors, a custom FPGA-based digital processing board with fast ADCs, and customkickerdrive amplifiers. The latest results from beam tests at ATF2 will be presented,including the system latency and correction performance. Copyright © 2012 by IEEE.